2014
DOI: 10.1007/s11916-013-0401-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary Headaches in Children Under the Age of 7 Years

Abstract: Recurrent headache is increasingly recognised in young children. Migraine and tension-type headache feature commonly amongst the primary headache disorders seen at this age. Headaches at this age are more likely than in older patients to be 'unclassifiable', possibly a reflection of the difficulties in obtaining a detailed headache history from a young child. Together with recent epidemiological data this review highlights the more prevalent primary headache types with advice on making a focussed headache asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…Although migraine is a common and crippling neurological disorder in pediatric populations, it has not received much attention in children younger than 7 years of age, with only a limited number of published studies describing the clinical and therapeutic features of migraine in this younger age group . Furthermore, symptoms with possible clinical and therapeutic implications such as osmophobia, allodynia, and cranial autonomic signs have not been reported in these studies .…”
mentioning
confidence: 99%
“…Although migraine is a common and crippling neurological disorder in pediatric populations, it has not received much attention in children younger than 7 years of age, with only a limited number of published studies describing the clinical and therapeutic features of migraine in this younger age group . Furthermore, symptoms with possible clinical and therapeutic implications such as osmophobia, allodynia, and cranial autonomic signs have not been reported in these studies .…”
mentioning
confidence: 99%
“…This finding may be related to the lower frequency of migraine in the younger patients ( P < .01 and the association of younger age with vomiting. Additionally, other studies reported a high rate of vomiting as one of the clinical characteristics of young patients with migraine …”
Section: Discussionmentioning
confidence: 96%
“…In the present study, vomiting was significantly associated with younger age at onset of migraine and at admission to the headache clinic. Accordingly, Abu‐Arafeh and Howells found that vomiting was present in 59% of patients in whom migraine first occurred before age 7 years. Min et al reported an association of vomiting with younger age in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Abu-Arafeh i Howell [6] zwracają uwagę na rosnącą ilość rozpoznań napadowych bólów głowy o cechach migrenowych czy napięciowych u dzieci najmłodszych poniżej 7. roku życia. Bóle te są w większości nieklasyfikowalne ze względu na trudności z uzyskaniem wiarygodnego wywiadu od tych dzieci.…”
Section: Postępy W Diagnostyce Bólów Głowy U Dzieci I Młodzieżyunclassified